THE INFLUENCE OF A TRANSFORMATIONAL LEADERSHIP STYLE, EXPERIENCE, WORK SATISFACTION AND ORGANIZATIONAL COMMITMENT TO ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN PUBLIC WORKS AND SPATIAL PLANNING OF KARIMUN REGENCY - Prayitno, Cahyo; Ngaliman, Ngaliman; Muliana, Heppy; Hizam, Nurul; Wayan Catra Yasa, I (RADJA PUBLIKA, 2022)
The purpose of this study was to determine the effect of Transformational Leadership Style, Experience Level, Job Satisfaction, Organizational Commitment to Organizational Citizenship Behavior at the Public Works and Spatial Planning Office of Karimun Regency. This type of research is descriptive quantitative. The sample population in this study amounted to 66 responden and the data collection technique used the technique of proportionate stratified random sampling where the technique is used if the population has members / elements that are not homogeneous and stratified proportionally. The data were collected using a questionnaire that had been tested for validity and reliability. Based on the research results, there are twelve conclusions that are relevant to the problems studied in this study.